2D materials and its heterostructured photocatalysts: Synthesis, properties, functionalization and applications in environmental remediation. Issue 6 (December 2021) - Garg, Anushka; Basu, Soumen; Shetti, Nagaraj P.; Reddy, Kakarla Raghava
Abstract: The pharmaceuticals and organic dyes form a large group of contaminants contributing to depleting the water quality and posing a threat to both flora and fauna. These contaminants are generally released from textile and other industrial processes. The recent spread of Covid-19 worldwide has encouraged the infected population to intake antibiotics and antivirals for their recovery as well as a non-infected group to boost their immunity and prevent the spread. As the intake rate increases, the release of eliminated pharmaceuticals into the water bodies increases. Therefore, several techniques have been developed for the efficient degradation of pharmaceuticals in water. In this review, a detailed contribution of different researchers and scientists for the efficient removal of several antibiotics such as chloramphenicol, chlortetracycline, ciprofloxacin, tylosin, etc. is explained. Various routes for both human and veterinary medicines have been explained in detail. An exhaustive collection of bibliographical data has been done with articles in respective domains. Two dimensional (2D) materials and their composites due to their magnificent properties have been in the limelight for ages and have been exploited for potential applications in different areas such as sensing, drug delivery, batteries, and most importantly wastewater treatment. Several techniques with the help of different 2D composites such as photocatalysis, visible light degradation, electrocatalysis, dielectric barrier discharge system, and sonocatalysis have been emphasized to gain knowledge about the current trend and future prospects. Graphical Abstract: ga1 Highlights: Types of 2D materials are classified and their functionalization methods. Importance of 2D materials for sustainable environment is discussed in depth. Major water pollutants include biomedical, textile dyes and other industrial waste. Environmental impact of pharmaceuticals (human and veterinary drugs) are analyzed. Detailed discussion of degradation efficiency of various 2D nanohybrids is studied.